Transmission Belts: On how young adults in Germany and Italy make meaning of mobility in transitions to work and adulthood - Sebastiano Benasso; Simone Castellani; Anna Cossetta; Christiane Dittrich; Andreas Walther (Social Work & Society, 2021)
In this article, four biographical narratives of young adults are explored concerning experiences of mobility in non-linear transitions to work. While the experiences of mobility unfold in different individual trajectories and contexts, the focus lies on the ways in which they are constructed and represented (both in the private and public realm) by narrations. Drawing on the accounts of young adults on their experiences of mobility in narrative interviews and personal blogs in four different studies in Italy and Germany, the article analyses how individuals reconstruct different representations of mobility in diverse socio-economic contexts and how narratives of mobility contribute to produce meaning as well as legitimation in the context of life course transitions. In this sense, narratives are understood as a "transmission belt" synchronising mobility, transitions and social change.